Determination of Phenol and Flavonoid Content and Total Anti-Oxidant for Abelmoschus Esculentus - Abdullah, Aisha Idriss; Ibrahim Ali Azaga; Fatima Ali Matoug; Mohamed Ali Alwahsh (Journal of Pure & Applied Sciences, 2024)
Abelmoschus esculentus is a vegetable crop with high nutritional value, Since it is rich in fibers and many important minerals and vitamins, in addition to flavonoid and phenolic compounds with high biological properties, which play an antioxidant role and are involved in many important activities in the body. The study aimed to estimate the phenolic and flavonoid content and the antioxidant activity of the okra plant. The method of aqueous extraction of the plant was followed. Qualitative and quantitative tests were conducted for the active compounds in the extract, in addition to measuring the total antioxidant capacity of the plant. The results showed that the plant contains some active elements such as flavonoids. , alkaloids, terpenes, tannins and saponins, and the quantitative determination of the plant content of flavonoids and phenolic compounds were tested, using the Folin-Ciocalteu reagent method and the AlCl3 aluminium chloride method, the results showed the plant contained high levels of flavonoids estimated at 639.9 – 662.8 mg/100 GA, while the extracted content of phenols was estimated at 336.84 – 367.26 mg/100 GA, and the antioxidant activity was estimated using the Phosphomolybdate Test, the results were estimated at g/2.02mg, and in the Hydroxyl Test, the results were 64.52%, 66.17%, and 82.16. % for concentrations of 20%, 40% and 60%. The study proves that the plant is rich in effective compounds and antioxidants.